Evaluation of the legal models applied in the formalization of rural property, in particular in the process of titling rural vacant land in Colombia - Cabrera Suárez, Lizandro Alfonso (DIXI, 2019)
Objective: This research makes an exhaustive analysis on the normative and jurisprudential evolution of the titling of rural land assets in Colombia.Methodology: Three objectives are proposed: the first is to identify and analyze historical and current normative antecedents that have regulated the theme of the titling of rural land assets in Colombia; the second, to identify and analyze the jurisprudential line of the Constitutional Court in the subject of the titling of vacant land assets of a rural character, based on the review of tutelage and constitutionality sentences issued by that corporation; the third, to analyze what was established in Law 160 of 1994 and the one consecrated in the Final Agreement for the End of the Conflict, regarding the titling of vacant lands of Colombia. In order to respond to each objective, a descriptive research design is proposed within the legal research approach.Results and conclusions: although in the area of agrarian reform in Colombia, it has been tried to move from a simple concept, based on land ownership, to an integral one that tackles rural issues in a totalitarian way, in practice, it has not yet been possible to develop , despite the normative efforts in the matter.
Keywords: normativity; jurisprudence; titling of vacant land assets